An integrated simulation paradigm for lifecycle-covering maintenance in the Industry 4.0 context. Issue 3 (2020) - Cimino, Chiara; Leva, Alberto; Negri, Elisa; Macchi, Marco
Abstract: The Industry 4.0 is pushing a fast evolution in all manufacturing operations under heterogeneous aspects. Maintenance, in all its numerous declinations along the life cycle of a production asset, is no exception. A myriad of decisions need taking—often on short time horizons, involving different physical and technological domains, and with limited knowledge available. A myriad of data sources need exploiting and interpreting—often poorly structured, requiring reconciliation, and affected by uncertainty. A lot of tools are therefore used—each one conceived for a specific purpose, often leveraging knowledge drawn from different cultures, and dealing with production assets' models that are hard to integrate with one another. We conjecture that the OOMS (Object-Oriented Modelling and Simulation) paradigm can help address such a tough scenario. In this paper we structure and motivate the statement just made, provide high-level supporting examples, and outline future work as for both research and technology.